Penilaian Persediaan Barang Dagang Beras Pada UD. Padi Emas Di Kota Ambon - Asrida, Wa; Tangke, Diar Muzna; Hariyati3, Tri Retno; Insan, Wa Ode (ISAS, 2025)
This study aims to analyze and compare the valuation of rice merchandise inventory at UD. Padi Emas in Ambon City is grouped using the FIFO (First-In, First-Out) method. Method with periodic and perpetual recording. UD. Padi Emas is a rice trading business located at Jl. Rijali No. 29, Karang Panjang Village, Sirimau District, Ambon City, Maluku, has been operating since 2013. UD. Padi Emas is one of the key trading businesses in Ambon City, so effective inventory management is crucial for the accuracy of financial reports and informed decision-making. The objective of this research is to analyze the valuation of rice merchandise inventory at UD. Padi Emas in Ambon City. This study employs a quantitative descriptive method with a case study approach. Data was collected through observation, interviews, and literature review. The analysis was conducted using both periodic and perpetual recording systems with the First-In, First-Out (FIFO) inventory valuation method for the period of February to June 2025. The results consistently show that the ending inventory value and Cost of Goods Sold (COGS) generated by both recording methods (periodic and perpetual) using FIFO are the same, with an ending inventory value of Rp9,875,000 and COGS of Rp178,180,000. This consistency confirms that the FIFO method provides accurate and reliable inventory valuation and helps minimize the risk of damaged rice as the first goods in are sold first. While this research also analyzed the periodic method, the perpetual inventory system is highly recommended. By implementing a perpetual system, UD. Padi Emas can monitor its rice stock continuously and accurately, which will aid in more effective decision-making and inventory planning. This system also allows for the early detection of any shortages or overages of rice in the warehouse and helps in the faster identification of potential losses or fraud. Adopting the perpetual inventory system will assist UD. Padi Emas in optimally manages its rice inventory, reducing losses from damaged rice and increasing operational efficiency. Keyword: Merchandise Inventory, Method FIFO